Kinerja Keuangan Sebelum dan Sesudah Penerapan Good Corporate Governance pada PT. Bank Pembangunan Daerah Bali - Odi Rezky Saputra, Ida Bagus; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p11, 2020)
This research is in the form of observations on PT Bank Pembangunan Bali which has implemented Good Corporate Governance. The data collection method uses documentation study data and literature study. This is intended to obtain a clearer picture in order to solve the problem under study. Analysis of the data used includes an analysis of financial performance based on liquidity ratios, profitability and solvency. The results of this study indicate an increase in financial performance after the implementation of Good Corporate Governance when viewed using Return on Assets, Operating Expenses / Operating Income, Capital Adequacy Ratio, Non-Performing Loans. Meanwhile, if viewed through the ratio of Loan to Deposit and Return on Equity the study found a decrease in performance after the implementation of Good Corporate Governance. Keywords: Good Corporate Governance; Financial Performance; Bank.